New approaches in oil spill mapping and emergency planning - Romero, A. F. [UNESP]; Fontes, R. F.C. [UNESP]; Oliveira, M. [UNESP]; Abessa, D. M.S. [UNESP] (My University, 2014)
During oil spill episodes, the oil may reach the coastal environments, despite efforts to retain and remove the oil from the water. Thus, response actions must be properly planned in order to minimize the environmental impacts caused by the oil. Contingency plans for oil spill accidents were developed in the 1970s and involve a set of steps that include environmental sensitivity index maps (ESI maps). At that time, this valuable tool represented advancement in action planning. Since then, however, contingency plans have used the ESI maps as a definitive planning solution, without combining them with other tools such as numerical modeling. The technological advances involved in numerical modeling, computational and geo-processing techniques, and access to a wide database through the internet, all allow for the introduction of advancements in oil spill response action plans. This chapter aims to present some of these new techniques in order to improve the classic approaches and provide more efficiency for emergency action plans. One of these techniques is the combination of ESI maps with information from numerical modeling of oil slicks and the probability that a given environment will be reached by the oil. This combination helps to generate maps of the indices of environmental vulnerability to oil (IEVO maps), which quickly and easily show areas that should receive priority protection after an oil spill. Another planning tool that may be used with the ESI and IEVO maps is the map of cleaning procedures and response actions. This map relies on the use of pictographic icons that represent the cleaning procedures recommended for each coastal environment. A careful definition of the recommended methods may keep the response actions from amplifying the damage caused by the oil, and their representation as icons on a map also allows for rapid visualization, and thus rapid decision making by officials responsible for emergency actions. These maps must also rely on solid information; thus, the assessment of biological resources of each coastal environment needs to be complete and deep. The use of GIS techniques to spatially display the biological information may help to identify more sensitive areas within a region that has already been classified using a given environmental sensitivity index. ESI maps that prioritize the representation of biological resources along the potentially affected areas provide an advancement in terms of the protection and mitigation of impacts on coastal ecosystems. These new approaches allow for better emergency planning move the classic approach forward, thus contributing to the mitigation of potential environmental impacts caused by oil spills.